2017
DOI: 10.1161/circheartfailure.117.004088
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Spousal Health and Outcomes in Heart Failure

Abstract: Background A diagnosis of heart failure (HF) often requires a comprehensive lifestyle change to maintain disease stability. When patients with HF are married, the spouse frequently assumes the caregiving role. Our objectives were to describe the health of spouses of married patients with HF, and examine if the health of a spouse impacts patient outcomes. Methods and Results We identified 905 patients that were married at the time of incident HF diagnosis in Olmsted County, Minnesota from 2000-2012. Using Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Future research will require larger samples of male surviving spouses to elucidate mechanisms by which bereavement effects may vary by gender. [46] Our findings should be interpreted with a number of potential limitations in mind. Because we used Medicare claims data to measure costs, we were limited to older spouses with FFS Medicare.…”
Section: Discussionmentioning
confidence: 91%
“…Future research will require larger samples of male surviving spouses to elucidate mechanisms by which bereavement effects may vary by gender. [46] Our findings should be interpreted with a number of potential limitations in mind. Because we used Medicare claims data to measure costs, we were limited to older spouses with FFS Medicare.…”
Section: Discussionmentioning
confidence: 91%
“…3,32–34 In 1 study evaluating caregivers of deceased patients with heart failure, they were found to be at increased risk of hospitalization and death themselves. 35 The impacts of heart failure on caregivers represents an opportunity for further study and intervention, particularly in a frail HFpEF population. 36…”
Section: Discussionmentioning
confidence: 99%
“…Although studies to date do not describe health of a spouse as impacting HF outcomes in patients, 31 the health of a patient with HF has been shown to impact the caregiving partner. 32 …”
Section: Discussionmentioning
confidence: 99%